Penerapan Otomasi Perpustakaan Menggunakan Senayan Library Management System (SLiMS) pada Perpustakaan SMA Negeri 12 Sinjai - Haruddin, Haruddin; Sukarman, Sukarman; Pratama, Indra Setya (Literatify: Trends in Library Developments, 2026)
This study examines the implementation of the Senayan Library Management System (SLiMS) as a form of library automation in SMA Negeri 12 Sinjai and analyzes its implications for service efficiency, information accessibility, collection management, and user satisfaction. Using a qualitative case study approach, data were collected through in-depth interviews, observations, documentation, and focus group discussions involving librarians, teachers, and students. The findings indicate that SLiMS contributes to faster service transactions, improved access to collections through OPAC, more systematic collection management, and higher levels of user satisfaction. Theoretically, this study extends the discourse on library automation by demonstrating that the success of automation in school libraries is not only determined by technological availability but also by user acceptance and institutional readiness. However, this study is limited to a single school context and relies primarily on qualitative data, which may restrict the generalizability of the findings. Future studies are encouraged to involve multiple sites and integrate quantitative measurements to strengthen comparative analysis.